Decolonising Heritage in South Asia
1 online resource (272 pages)
Keywords: This volume cross-examines the stability of heritage as a concept. It interrogates the past which materialises through multi-layered narratives on monuments and other objects that sustain cultural diversity. It seeks to understand how interpretations of “monuments” as “texts”are affected at the local level of experience, even as institutions such as UNESCO work to globalise and fix constructs of stable and universal heritage. Shifting away from a largely Eurocentric concept associated with architecture and monumental archaeology, this book reassesses how local and regional heritage needs to be balanced with the global and transnational. It argues that material objects and monuments are not static embodiments of culture but are, rather, a medium through which identity, power and society are produced and reproduced. This is especially relevantin South and Southeast Asian contexts, where debates over heritage often have local, regional and national political implications and consequences. Reevaluating how traditional valuation of monuments and cultural landscapes could help aid sustainability and long-term preservation of the heritage, this book will be useful for scholars and researchers ofSouth and SoutheastAsian history, heritage studies, archaeology, cultural studies, tourism studies and political history as well.